2021
DOI: 10.1159/000519826
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Metabolic Comorbidities in Acute Pancreatitis and Its Impact on Early Gastrointestinal Symptoms during Hospitalization: A Prospective Cohort Study

Abstract: <b><i>Background:</i></b> The prevalence of chronic comorbidities is increasing worldwide, and this has been paralleled by a growing interest in how these comorbidities affect patients with acute pancreatitis. The aim was to investigate the associations between pre-existing diabetes mellitus, obesity, metabolic syndrome, and gastrointestinal symptoms during the early course of acute pancreatitis. <b><i>Methods:</i></b> This was a prospective cohort study of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…5 A previous study revealed that more than 60% of AP patients had at least one major metabolic comorbidity, which was similar to our findings (53.9% hyperglycemia and 73.9% hypertriglyceridemia). 26 Among the components of metabolic syndrome, hyperglycemia and hypertriglyceridemia are the two most common metabolic abnormalities, which have frequently been reported to be associated with worse prognosis in AP. 8,9,27 Furthermore, both hyperglycemia and hypertriglyceridemia have been linked to impaired immune function, 10,12 potentially increasing the incidence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…5 A previous study revealed that more than 60% of AP patients had at least one major metabolic comorbidity, which was similar to our findings (53.9% hyperglycemia and 73.9% hypertriglyceridemia). 26 Among the components of metabolic syndrome, hyperglycemia and hypertriglyceridemia are the two most common metabolic abnormalities, which have frequently been reported to be associated with worse prognosis in AP. 8,9,27 Furthermore, both hyperglycemia and hypertriglyceridemia have been linked to impaired immune function, 10,12 potentially increasing the incidence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antidiabetic medications were included in statistical models. This study also did not assess other possible confounders (e.g., inflammatory markers, intra-pancreatic fat deposition), which may affect glucose metabolism and insulin traits following AP [ 101 , 102 , 103 , 104 , 105 , 106 ]. Due to the relatively small sample size of the present study and results not being corrected for multiple testing, there is a risk of type I error.…”
Section: Discussionmentioning
confidence: 99%
“…40 female patients with metabolic syndrome and 40 healthy women, with age-range 35 to 60 years, participated in the study. The International Diabetes Federation reported in 2005 that the global consensus on metabolic syndrome served as the foundation for the diagnosis of metabolic syndrome 19,20 . In addition to a patient's BMI above 30 kg/m 2 , to be diagnosed with metabolic syndrome, any two of the following four requirements have to be satisfied: 1) Triglyceride levels are high (150 mg/dL) (or particular treatment for this lipid imbalance).…”
Section: Study Subjectsmentioning
confidence: 99%